1986
DOI: 10.1590/s0034-89101986000500005
|View full text |Cite
|
Sign up to set email alerts
|

Esquistossomose mansônica em camundongos experimentalmente subnutridos

Abstract: MAGALHÃES, L.A. et al. Esquistossomose mansônica em camundongos experimentalmente subnutridos.Rev.Saúde públ., S.Paulo, 20: 1986. RESUMO:Realizou-se estudo sobre o desenvolvimento da esquistossomose mansônica em camundongos submetidos à dieta hipoprotéica. Foram constituídos 4 grupos de Mus musculus "Swiss" da seguinte forma: 1) não infectados, normoprotéicos; 2) infectados, normoprotéicos; 3) não infectados, hipoprotéicos e 4) infectados, hipoprotéicos. Os animais foram sacrificados com 60 dias de infecção, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…This has been previously demonstrated in adult animals (Magalhães et al 1986, Coutinho et al 2003, Coutinho 2004 due to the inflammatory process caused by S. mansoni eggs (Mota & Sleigh 1984, Sleigh et al 1986). Liver pathology around mature eggs depends on, among other factors, the host nutritional status (Coutinho et al 1997, Oliveira et al 2004).…”
Section: Table IVsupporting
confidence: 55%
See 1 more Smart Citation
“…This has been previously demonstrated in adult animals (Magalhães et al 1986, Coutinho et al 2003, Coutinho 2004 due to the inflammatory process caused by S. mansoni eggs (Mota & Sleigh 1984, Sleigh et al 1986). Liver pathology around mature eggs depends on, among other factors, the host nutritional status (Coutinho et al 1997, Oliveira et al 2004).…”
Section: Table IVsupporting
confidence: 55%
“…Thus, schistosome maturation (Kanuft & Warren 1969), worm burden and oviposition reduction (Akpom 1982, Rocha 1982, Magalhães et al 1986, Neves et al 2001, as well as the production of altered eggs, have been observed in nutritionally restricted mice (Akpom & Warren 1975). Our previous report showed that the pre-patent period and the kinetics of egg excretion were similar to well-fed controls (Simões et al 2002).…”
Section: Table IVmentioning
confidence: 99%
“…Mice were experimentally infected and submitted to a low-protein diet using the BH strain of S. mansoni . In spite of the reduced number of hepatic granulomas, as well as a reduction in the size of the granuloma, mortality rates among the animals were high [29]. Recent studies [30] used different strains of mice and established an association between malnutrition and the development of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…He also provided a detailed description of the morphology of Schistosoma mansoni adult worms 8 . Since its discovery, Schistosoma mansoni has been the subject of intense investigation, describing the features of adult worm based on light microscopy [9][10][11][12][13] . With the advances in microscopy technology, confocal laser scanning microscopy has become an invaluable tool for helminthology, mainly for schistosomiasis mansoni studies [14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specimens deposited within helminthological collections permit further revisiting studies that may lead to new morphological descriptions 25 . In more recent history, both light microscopy and confocal laser scanning microscopy experienced advances that have been used to develop further studies regarding the morphology of adult worms of S. mansoni 9,10,11,21 . In this study, specimens of S. mansoni deposited in the Helminthological Collection of the Oswaldo Cruz Institute were re-examined.…”
mentioning
confidence: 99%